2003
DOI: 10.1002/ijc.10898
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent variations of human and rat colon myofibroblasts in culture: Influence on their functional interactions with colon cancer cells

Abstract: Epithelial-mesenchymal interactions play a pivotal role in colon cancer invasion and metastasis. We aimed at elucidating the impact of long-term cultivation on the phenotypic and functional characteristics of primary fibroblasts and their interaction with the human colon adenocarcinoma cell line LoVoC5. We used fibroblasts from human colon tumor tissue, normal human colon mucosa, rat normal colon and 2 rat colon-derived myofibroblast cell lines, MIC316 and MG. The following parameters were studied: cell shape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 27 publications
0
14
0
4
Order By: Relevance
“…Likewise, FGF-1ϩH strongly inhibited (when used simultaneously) and reverted (when used subsequently) the TGF-␤1-induced switching of the human lung fibroblasts to myofibroblasts that was accompanied by a change in cell morphology from a typical flattened, irregular shape characteristic of a myofibroblast-like phenotype to an elongated, spindle-shaped appearance (17,26). The effect of FGF-1ϩH on myofibroblast phenotype was demonstrated by several complementary techniques, including flow cytometry, immunocytochemistry, and quantification of ␣-SMA by real-time RT-PCR and Western blot.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Likewise, FGF-1ϩH strongly inhibited (when used simultaneously) and reverted (when used subsequently) the TGF-␤1-induced switching of the human lung fibroblasts to myofibroblasts that was accompanied by a change in cell morphology from a typical flattened, irregular shape characteristic of a myofibroblast-like phenotype to an elongated, spindle-shaped appearance (17,26). The effect of FGF-1ϩH on myofibroblast phenotype was demonstrated by several complementary techniques, including flow cytometry, immunocytochemistry, and quantification of ␣-SMA by real-time RT-PCR and Western blot.…”
Section: Discussionmentioning
confidence: 97%
“…The effects of FGFs are mediated by binding to the FGF receptor (FGFR) family of receptor tyrosine kinases (19,30,44). Heparin and heparan sulfate glycosaminoglycans act as low-affinity receptors and are part of a dual-receptor system, which, along with a cell surface tyrosine kinase receptor, transduces ligand activation along appropriate cytosolic and nuclear pathways (20,21,26). FGF-1, the first described of this family, regulates cell growth and differentiation and participates in several physiological processes, including angiogenesis and tissue repair (19).…”
mentioning
confidence: 99%
“…Only early-passage fibroblast cultures are used in experiments to more closely simulate their in vivo phenotype. It has been shown that early-passage (below passage 9) colonic primary fibroblasts maintain many of their in vivo characteristics, including expression of alpha-smooth muscle actin, collagen IV and laminin 1 [28]. Multiple NAF and CAF cultures were utilized because of potential variation among fibroblasts from different individuals and different breast cancers.…”
Section: Methodsmentioning
confidence: 99%
“…Cluster II includes many genes that encode secretory proteins and genes involved in cell matrix or matrix modeling (e.g., Fibronectin, TIMP3, ADAMTS1, and TAGLIN). Some of these genes (including Fibronectin and TAGLIN) have been found to be expressed by myofibroblasts as well as smooth muscle cells (11,12). Therefore, we suspect that genes in this cluster most likely represent genes that are expressed by cryptic stromal cells.…”
Section: Gene Expression Signatures Of Human Colon Top and Bottom Cryptmentioning
confidence: 98%